Generalizing the Taylor principle: Comment - Roger E. A. Farmer; Daniel F. Waggoner; Tao Zha (Federal Reserve Bank of Atlanta, 2008)
Davig and Leeper (2007) have proposed a condition they call the generalized Taylor principle to rule out indeterminate equilibria in a version of the New Keynesian model, where the parameters of the policy rule follow a Markov-switching process. We show that although their condition rules out a subset of indeterminate equilibria, it does not establish uniqueness of the fundamental equilibrium. We discuss the differences between indeterminate fundamental equilibria included by Davig and Leeper's condition and fundamental equilibria that their condition misses.
Keywords: E52; 330; bounded solutions; multiple fundamental equilibria; historical dependence